تطوير مواد تعليم مهارة الاستماع لطلاب الفصل الدراسي الأول بقسم تعليم اللغة العربية كلية علوم التربية والتعليم جامعة سونان أمبيل الإسلامية الحكومية سورابايا - Mushlih Shafiyullah (UIN Maulana Malik Ibrahim Malang, 2021)
There were materials in teaching learning process of listening class in ArabicLanguage Education Department of Islamic University Sunan Ampel Surabaya whichconsist of listen to Arabic language culture recording purely without any addition of Indonesian language culture. In case, there was culture shock between the teaching learning and the student's culture.The qualitative method chosen to describe the characteristics of teaching materials before being developed and to identify the development of teaching materials. The researcher also used a quantitative method to determine the effectiveness of teaching materials development. The population and the sample is class C and D amount 44 students. While the data collection tools in this research are observation, interviews and tests. The hypothesis proposed in this study is material development that has the effectiveness for students to increase the Arabic language listening skills. The results of this research are: 1) Teaching materials before being developed Is consists of a recording that containing the text with a native speaker without any Indonesian culture and still neatly packed in one book. 2) The researcher improved the materials by pay attention to the students culture, and then some of them being maintained, replaced or held because did’nt exist previously. 3) Teaching materials development have the effectiveness. Proven from the value t0 (5,154) is greater than tt 5 % level of significant amount 2.018 and 1 % level of significant amount 2,698. Then, Ho isrejected and Ha is accepted. In other words, teaching materials that has been developed are effectively improved the listening student's intelegence.